2016
DOI: 10.1002/polb.24058
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and self‐assembly of well‐defined linear heptablock quaterpolymers

Abstract: Two well‐defined heptablock quaterpolymers of the ABCDCBA type [Α: polystyrene (PS), B: poly(butadiene) with ∼90% 1,4‐microstructure (PB1,4), C: poly(isoprene) with ∼55% 3,4‐microstructure (PI3,4) and D: poly(dimethylsiloxane) (PDMS)] were synthesized by combining anionic polymerization high vacuum techniques and hydrosilylation/chlorosilane chemistry. All intermediates and final products were characterized by size exclusion chromatography, membrane osmometry, and proton nuclear magnetic resonance spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…Furthermore, it should be mentioned that in such ABC linear terpolymers of the PS- b -PB 1,4 - b -PI 3,4 sequence our research group has managed [ 48 ] to identify the core-shell DG morphology concluding to the fact that the PI segment with the specific percentage of 3,4-microstructure is actually leading to a relatively high Flory–Huggins interaction parameter not only with PS but also with PB 1,4 . We have also demonstrated the stability of the three-phase four-layer lamellar structure by synthesizing heptablock quaterpolymers of the sequence PS- b -PB 1,4 - b -PI 3,4 - b -PDMS- b -PI 3,4 - b -PB 1,4 - b -PS [ 49 ]. The results from this specific work [ 49 ] indicated that the PI 3,4 and PDMS blocks are miscible, verifying our assumption of high value for the Flory–Huggins interaction parameter between the specific PI and PS or PB 1,4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it should be mentioned that in such ABC linear terpolymers of the PS- b -PB 1,4 - b -PI 3,4 sequence our research group has managed [ 48 ] to identify the core-shell DG morphology concluding to the fact that the PI segment with the specific percentage of 3,4-microstructure is actually leading to a relatively high Flory–Huggins interaction parameter not only with PS but also with PB 1,4 . We have also demonstrated the stability of the three-phase four-layer lamellar structure by synthesizing heptablock quaterpolymers of the sequence PS- b -PB 1,4 - b -PI 3,4 - b -PDMS- b -PI 3,4 - b -PB 1,4 - b -PS [ 49 ]. The results from this specific work [ 49 ] indicated that the PI 3,4 and PDMS blocks are miscible, verifying our assumption of high value for the Flory–Huggins interaction parameter between the specific PI and PS or PB 1,4 .…”
Section: Introductionmentioning
confidence: 99%
“…We have also demonstrated the stability of the three-phase four-layer lamellar structure by synthesizing heptablock quaterpolymers of the sequence PS- b -PB 1,4 - b -PI 3,4 - b -PDMS- b -PI 3,4 - b -PB 1,4 - b -PS [ 49 ]. The results from this specific work [ 49 ] indicated that the PI 3,4 and PDMS blocks are miscible, verifying our assumption of high value for the Flory–Huggins interaction parameter between the specific PI and PS or PB 1,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 summarizes the data on already reported linear triblock terpolymers in the literature [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ], and, more specifically, block sequence, number (or weight) average molecular weight range and the annealing conditions used, together with the corresponding reference. It is straightf...…”
Section: Introductionmentioning
confidence: 99%
“…The microstructures of the polydienes are similar (as calculated by proton nuclear magnetic resonance spectroscopy, 1 H-NMR spectroscopy). Full detailed synthesis of the terpolymers is described in the literature [35][36][37]. Scheme 1 shows the reactions for the synthesis of the triblock terpolymers.…”
Section: Block Copolymer Synthesismentioning
confidence: 99%
“…The triblock terpolymers displayed strongly incompatible and microphase separated components, (PS, PB 1,4 , and PI 3,4 ), where the two polydienes exhibit specific geometric isomerisms (high −1.4 for PB (~92%) and relatively high −3.4 for PI (~60%)). More specifically, PB exhibits approximately 92% −1.4 microstructure and 8% −1.2, whereas the PI is enriched in −3.4 microstructure (~60%),~25% corresponds to −1.4, and~15% to −1.2 microstructures, respectively [35][36][37]. The incorporation of iron oxide NPs (IONPs) and how their presence affects the generated terpolymer/NPs hybrid structure in comparison to corresponding diblock copolymer/NPs systems is discussed.…”
Section: Introductionmentioning
confidence: 97%